Profiles of dual language education in the 21st century - Arias, M. Beatriz; Fee, Molly 1986- (CAL series on language education, 2018)
"In the last 20 years dual language education programs have increased in number and expanded in range, spanning pre-K through high school. This book examines the key attributes of successful dual language programs, as well as the challenges and opportunities involved in extending the dual language instructional model to pre-K and secondary settings"--Provided by publisher.